Financial stress index, growth and price stability in India: some recent evidence. Issue 2 (3rd April 2021) - Sahoo, Jayantee
Abstract: In this paper, an aggregate financial stress index for India is constructed by taking monthly data from different segments of the financial market like money market, bond market, equity market, foreign exchange market, and the banking sector, for the period March 2007 to December 2016. The interrelationship and feedback effect between financial stress, economic growth and price stability are tested by using correlation and an unrestricted VAR model. The impulse response analysis shows that financial stress leads to a decline in growth after a lag period and a higher growth rate for a longer period of time increases stress in the financial system. The variance decomposition result indicates that the contribution of FSI to the variation of other variables are not much high, whereas other variables can affect FSI to some extent. In the Short-run price stability increases financial stress but in the long run, the result is the opposite.